PENGEMBANGAN YOUTH CENTER SEBAGAI DESTINASI WISATA BERBASIS SPORT PRENEUR DI DESA BANJARWARU KABUPATEN LUMAJANG - Sunandes, Aris; Zamrodah, Yuhanin; Puspitorini, Palupi; Lisaria Putri, Rumanintya; Fauziyah, Fauziyah (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
Banjarwaru Village, Lumajang District has the potential to develop preneur sport-based tourist destinations. The purpose of this research is to provide guidance and training for human resources, provide tourism management training in order to strengthen the concept of developing a youth center as a sport preneur-based tourist destination and training in marketing management to support the achievement of market share. The research method uses a qualitative descriptive method. The results of the study show that the ability of the community's human resources has begun to shift from those who used to only work as farmers to become entrepreneurs (entrepreneurs) in the tourism sector, to become people who are skilled and have creativity in tourism products. Banjarwaru Village has carefully planned tourist destinations, namely the locations have been mapped for sports facilities such as soccer facilities and rivers used for rafting with all existing facilities and built shops for local people to be entrepreneurs in the area around sport preneurs and carry out tourism marketing. either through the village web, Ig, fb, wa and brochures so that they can attract tourists to travel in Banjarwaru Village.